Mastering illiquidity : risk management for portfolios of limited partnership funds - Cornelius, Peter , 1960- (John Wiley & Sons, 2013)
Arms investors with powerful new tools for measuring and managing the risks associated with the various illiquid asset classes. This book provides an overview of illiquid fund investments, focusing on what the main risks of these asset classes are and how to measure those risks in today's regulatory environment